Hemophagocytic lymphohistiocytosis (HLH) secondary to disseminated histoplasmosis in the setting of Acquired Immunodeficiency Syndrome (AIDS) - Asanad, Samuel (Med Mycol Case Rep, 2018)
Hemophagocytic lymphohistiocytosis (HLH) is a rare and aggressive disease involving immune system over-activation leading to hemophagocytosis. HLH requires early diagnosis and prompt treatment initiation, especially in patients with Acquired Immunodeficiency Syndrome (AIDS). We present a case of a middle-aged male with AIDS and renal failure, who developed HLH secondary to disseminated histoplasmosis. Etoposide chemotherapy as recommended by the HLH 2004 Guidelines was deferred and treatment focused instead on anti-fungal therapy. Anti-retroviral therapy followed thereafter.